2019
DOI: 10.1111/jvs.12773
|View full text |Cite
|
Sign up to set email alerts
|

Lichens facilitate seedling recruitment in alpine heath

Abstract: Questions How do mat thickness, physical structure and allelopathic properties of terricolous mat‐forming lichens affect recruitment of vascular plants in dwarf‐shrub and lichen heath vegetation? Location The mountains of Dovrefjell, central Norway. Methods In autumn, seeds of ten vascular plant species were collected and sown in a common garden experiment with mats of six lichen species and bare soil controls as experimental treatments. We recorded growing season soil temperature and moisture, and seedling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Although clonal species can persist for long periods, long‐term vegetation dynamics depend increasingly on changes in community composition and hence successful seedling recruitment. Seedling recruitment is expected to depend on microclimatic conditions (Walck et al 2011) and on species interactions (Fayolle et al 2009, Milbau et al 2013, Nystuen et al 2019), both of which are likely to be affected by ongoing environmental changes. While seed production and germination in cold biomes are often found to respond positively to warmer temperatures, at least when sufficient soil moisture is available (Milbau et al 2009, Klady et al 2011, Walck et al 2011), seedling survival and establishment are in turn thought to be sensitive to droughts associated with warm weather (Moles and Westoby 2004, Fenner and Thompson 2005, Leck et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although clonal species can persist for long periods, long‐term vegetation dynamics depend increasingly on changes in community composition and hence successful seedling recruitment. Seedling recruitment is expected to depend on microclimatic conditions (Walck et al 2011) and on species interactions (Fayolle et al 2009, Milbau et al 2013, Nystuen et al 2019), both of which are likely to be affected by ongoing environmental changes. While seed production and germination in cold biomes are often found to respond positively to warmer temperatures, at least when sufficient soil moisture is available (Milbau et al 2009, Klady et al 2011, Walck et al 2011), seedling survival and establishment are in turn thought to be sensitive to droughts associated with warm weather (Moles and Westoby 2004, Fenner and Thompson 2005, Leck et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our study does show that the high albedo of lichens is not leading to lower soil temperatures below lichens than below shrubs during the growing season. Since recent studies have shown that differences in color, and therefore albedo, did not even cause a difference in soil temperature between lichen species (Nystuen et al, 2019;Van Zuijlen et al, 2020), it is unlikely that albedo is an important factor determining the difference in soil temperature between the two different vegetation types. Instead, the marked differences in canopy structure between lichens and shrubs are a more essential factor.…”
Section: Synthesismentioning
confidence: 99%
“…Multiple studies have discussed the cooling capacity of lichens on the underlying soil, and have argued that this cooling capacity is a result of their high albedo and the insulating properties of lichens due to their low conductivity. However, most studies measured or modelled lower soil temperatures below lichens in relation to bare soil or disturbed lichens (Beringer et al, 2001;Gold et al, 2001;Porada et al, 2016;Nystuen et al, 2019;Van Zuijlen et al, 2020), but the comparison with another vegetation type has rarely been made. Our study shows that the cooling capacity of lichens does not lead to a lower soil temperature compared to shrubs.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Small-scale disturbances, by removing or reducing the abundance of competitors, generate new microhabitats suitable for seedling emergence and establishment (Milbau et al, 2013;Nystuen et al, 2014;Lembrechts et al, 2016). However, severe disturbances can counteract the benefits of reduced competition, for instance when it leads to too hot and too dry soils that can be detrimental for tree seedlings (Kambo and Danby, 2018;Nystuen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%